HOMEPAGE APPLICATIONS GROUP BAND NOTHING ELSE USING MACROMEDIA FLASH MX - Apit Sturdy Haryanto; Ire Puspa W., SKom, MMSi (Jurnal Sistem Informasi, 2007)
Internet increasingly being used by people around the world to obtain information.Because of extensive coverage, the internet is ideal for the medium used to spreadinformation globally. Hjomepage have a function as a source of information, services,music, entertainment, education, and others. The role of the homepage in theinformation age as it is now very helpful in disseminating information quickly.Therefore, in scientific writing, the author makes a homepage which consists of bandsthat made nothing else using Macromedia Flash MX, which are expected to helpprovide information more quickly to the fans of bands commonly known nothing elsenothing else on the fans particular.